Media representation of Venezuelan migrants in Latin America: bibliometric analysis of pre- and post-pandemic studies - Camacho Estrada, Sara Nidhya; López Zurita, Héctor Santiago; Valencia Núñez, Edison Roberto; Trujillo Ronquillo, Danilo Fabricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This bibliometric analysis examined scientific production on Venezuelan migration in social networks in Latin America (2016-2025), processing 27 documents through systematic searches in Scopus, Web of Science, and Google Scholar using R. Results showed irregular growth with inflection in 2019 and consolidation in 2022-2023, evidencing regional asymmetry where Colombia led with 36 publications versus Ecuador with 3. Journal of Migration and Health and PLOS ONE emerged as central sources. COVID-19 constituted an investigative catalyst diversifying approaches toward interdisciplinary perspectives. It is concluded there is need for regional scientific strengthening and findings provide comprehensive cartography to guide future research and evidence-based policies.